PERANAN PENYULUH PADA USAHATANI PADI DI MASA PANDEMI COVID-19 DI DESA SAMBORA KECAMATAN TOHO KABUPATEN MEMPAWAH - Ellyta Ellyta; Ekawati Ekawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The purpose of this study was to determine the role of field extension workers on the productivity of rice farming. During the Covid-19 pandemic, physical contact and social contact were greatly reduced, it had an impact on the role that extension workers. To measure the data on the role of the extension worker, a Likert scale is used.. The results showed that a slowdown in extension activities, indicated by an average of over 70% of farmers saying there was no extension to farmers individually or in groups. The level of the role of the extension worker is 1.84 which is included in the Medium category. This means that from the overall average value of the role of the extension agent starting from the extension agent as an advisor, as an organizer, as a technician, as a liaison and as an agent of renewal, the role is sufficient for farmers.